Malignant peripheral nerve sheath tumor with rhabdoid features arising in the temporal region of a patient suffering from neurofibromatosis 1 - A case report - Amer,Hatem Wael (2022)
Abstract The malignant peripheral nerve sheath tumor is one of the rare sarcomas that have a challenging diagnosis. It occurs independently with neurofibromatosis type 1. Some studies referred that malignant peripheral nerve sheath tumor attains a worse prognosis when it occurs in the head and neck region. In the reported case, a male patient with neurofibromatosis type 1 manifestations presented with a large mass in the temporal region. Based on the clinical history, histopathology, and immunohistochemical findings, the lesion was diagnosed as a low-grade malignant peripheral nerve sheath tumor with rhabdoid features. Surgical resection followed by intensity-modulated radiotherapy was the treatment of choice.